STRATEGI PENERJEMAHAN BAHASA ARAB YANG BERTERIMA DAN MUDAH DIPAHAMI - Dafik Hasan Perdana (Jurnal Bahasa Lingua Scientia, 2017)
To produce an acceptable work of translation that is easily understood, an interpreter is required to have a strong word sense in order to determine whether the translation is in accordance with the tastes and expectations of the target reader or not. Likewise in translating Arabic, an interpreter is expected to be the bridge between the author of the source language to the target of language readers. In other words, the translator instead of summarizing a text into a new writing, he/she must be able to be a facilitator of communication transmitter of messages contained in the source language to the target language appropriately. Hence, he/she is able to produce a work of translation which is free from any literal translations and language structure rigid. However, in fact, some Indonesian translations to Arabic –or the vise verse- are still stiff and unfamiliar to the readers of the source language or the readers of the target language.